Activin A immunoexpression as predictor of occult lymph node metastasis and overall survival in oral tongue squamous cell carcinoma. Issue 4 (3rd April 2014) - Kelner, Natalie; Rodrigues, Priscila Campioni; Bufalino, Andreia; Fonseca, Felipe Paiva; dos Santos‐Silva, Alan Roger; Miguel, Marcia Cristina Costa; Pinto, Clóvis Antonio Lopes; Leme, Adriana Franco Paes; Graner, Edgard; Salo, Tuula; Kowalski, Luiz Paulo; Coletta, Ricardo D.
ABSTRACT: Background: The presence of regional lymph node metastasis has an important impact on clinical management and prognostication of patients with oral tongue squamous cell carcinoma (SCC). Approximately 30% to 50% of patients with oral tongue SCC have regional metastasis at diagnosis, but the limited sensibility of the current diagnostic methods used for neck staging does not allow detection of all cases, leaving a significant number of undiagnosed metastasis (occult lymph node metastasis). In this study, we evaluated whether clinicopathologic features and immunohistochemical detection of carcinoma‐associated fibroblasts (CAFs) and activin A could be predictive markers for occult lymph node metastasis in oral tongue SCC. Methods: One hundred ten patients with primary oral tongue SCC, who were classified with early stage tumor (stage I and II) and received surgical treatment with elective neck dissection, were enrolled in the study. Results: Among all examined features, only high immunohistochemical expression of activin A was significantly associated with presence of occult lymph node metastasis ( p = .006). Multivariate survival analysis using the Cox proportional hazard model showed that the expression of activin A was an independent marker of reduced overall survival with a 5‐year survival of 89.7% for patients with low expression compared to 76.5% for those with high expression (hazard ratio [HR], 2.44; 95% confidence interval [CI], 1.55–3.85; p = .012). Conclusion: Our results demonstrated that immunodetection of activin A can be useful for prognostication of oral tongue SCC, revealing patients with occult lymph node metastasis and lower overall survival. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 479–486, 2015